Turning a Deaf Ear: Acoustic Value in the Assessment of Heritage Landscapes - O'Connor, Penelope (Routlegde, 2011)
Aesthetic value is one of the fundamental criteria used to determine the cultural heritage significance of important places. In Australia, however, cultural heritage has had only a limited engagement with theories on aesthetics, and as a result, no practical methodology has been developed to identify, describe and assess the acoustic dimension of aesthetic value. This paper critiques the literature on aesthetics that cultural heritage has focused on to date, highlighting its emphasis on the visual qualities of place over other multi-sensory understandings. Recent research into acoustics, particularly based on the concept of the soundscape, is explored in order to develop a qualitative methodology to assist heritage practitioners and others in understanding, describing and evaluating the acoustics of place. The applicability of this approach is demonstrated through the analysis of two cultural landscapes in the south-west of Western Australia.